Muhammad Abduh’s Role in al-Waqa’i‘ al-Misriyyah an Official Egyptian Gazette - Nabil Amir, Ahmad; Abdul Rahman, Tasnim (Alif Lam : Journal of Islamic Studies and Humanities, 2025)
The article discusses the role of Muhammad Abduh (1849-1905) in his illustrious career as leading editor of al-Waqā’i‘ al-Misrīyya ( الوقائع المصرية) [Egyptian Events] an official Egyptian gazette. It brings profound impact in the field of journalism in the context of rising popularity of al-Waqā’i‘ al-Misrīyyah during his editorship (1880-1882), that established its reputation as leading Egyptian newspapers highlighting unprecedented socio-cultural and religious reform undertaken by the establishment, in the midst of phenomenal and competitive growth of independent press. His writing was instrumental in developing national consciousness toward modernization program and influencing public opinion in Egypt. It allowed for better development of formidable national spirit and awakening their higher ideal and convention in language, literature and culture as well as mobilizing social awareness of intense political and cultural dynamics. His career span the period of Riyad Pasha and Sharif’s administration and subsequent political unrest. The research is based on qualitative and documentation technique. It reviewed accumulated data by way of descriptive, analytical, historical and comparative method. The finding shows that al-Waqā’i‘ has assumed unprecedented influence and success during the editorship of Abduh through his dynamic and productive articles and rigorous daily basis of production of the newspaper